If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 7y = 126 Solving 2x + 7y = 126 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7y' to each side of the equation. 2x + 7y + -7y = 126 + -7y Combine like terms: 7y + -7y = 0 2x + 0 = 126 + -7y 2x = 126 + -7y Divide each side by '2'. x = 63 + -3.5y Simplifying x = 63 + -3.5y
| m/8=16 | | 11x^2-47y+12=0 | | 12-17=89 | | -5+1/4m=-7 | | 72=x+15 | | 1/2(6x+4)=2x-11 | | 4y^2-15y+9=0 | | 18-3x(4+(-8))+5x=10x-2 | | 2(x+-9)=-10 | | -5+1/4(-2)=-7 | | 8(3-y)-4=-(2-y)-9y | | 2m+1/3-m-6/4=2m+4/8+2 | | x^2+7xy^2=0 | | 15+3x=21 | | 8*x=17/2 | | 2m+1/3-m-6/4=2m | | 1/2y+x=-10 | | -3x+3=-2x+1 | | 4(3-2x)+2=2 | | (5b)*(-9x)= | | 2*cosx*sinx-cosx=1 | | 7(2+5h)=-17 | | C+9=18 | | 7(2+5h)=-71 | | 6+1.25a=1.1a | | (x^2+12x+40)/(x+7) | | 13/5=n | | .02-.05x+.3x=-.68 | | 16-4j+12j-19=-3j+2-7j+4 | | -12y+8=-11y+9 | | 3.2x=4x+16 | | x^2+1x-72=0 |